Reticulated acanthoma with sebaceous differentiation: another sebaceous neoplasm associated with Muir–Torre syndrome?. (8th May 2013) - Shon, Wonwoo; Wolz, Michael M; Newman, Catherine C; Bridges, Alina G
Abstract Reticulated acanthoma with sebaceous differentiation (RASD) represents a rare benign cutaneous epithelial neoplasm with sebaceous differentiation. There has been much speculation about the relationship between RASD and Muir–Torre syndrome (MTS). We report a 53 year‐old man who presented with RASD in addition to a prior history of sebaceous adenomas. Immunohistochemically, the tumour cells in the RASD and sebaceous adenomas showed a significantly reduced MSH6 protein expression, whereas there was no loss of MLH1, MSH2 and PMS2. This benign neoplasm, which can be mistaken for various other cutaneous lesions with sebaceous differentiation, deserves wider recognition for its possible association with MTS.